Ihya' 'ulumiddin: menghidupkan ilmu ilmu agama Islam - Imam Al_Ghazali (Asy Syifa, 1993)
Oen, Jil. 1-9=c.1/tr, jil.3=c.2; jil.4=c.2; jil.8=c.2; jil.9=c.2/tr, jil.1=c.2; jil.2=c.2; jil.3=c.3; jil.4=c.3; jil.5=c.2; jil.6=c.2; jil.7=c.2/ rt, jl.3=c.4/oen, jil.3=c.5